Antibacterial activity of cocoa bean husk extract on the growth of Streptococcus alpha - Siswanto, Vonny Gunawan; Mahendra, Putri Kusuma Wardhani; Kuswandari, Sri (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: Streptococcus alpha is the most common bacteria found in dental plaques of children and roled as pioneer bacteria in plaque formation. One of the natural agents which has antibacterial activity is cocoa bean husk (Theobroma cacao, L.). This study aimed to analyze antibacterial activity of cocoa bean husks extract concentration 12.5%, 25%, 37.5% and 50% on the growth of S. alpha. Methods: This study was a laboratory experiment conducted in March, 2021 at Microbiology Laboratory, Faculty of Medicine Universitas Negeri Surakarta. The bacteria was isolated from the buccal tooth surface plaque of caries-free-9-years-old girl, then incubated on the blood agar medium to grow the S. alpha. The extract of cocoa bean husk concentration 12.5%, 25%, 37.5%, 50% and 0,2% Chlorhexidine Gluconate(CHX) as positive control were used to identify the antibacterial activity by measure the diameter ofinhibition zone growth of S. alpha in the blood agar medium. The data was analyzed using one-way Anova. Results: Significant differences were found among the treatment groups (p<0.05). The highest mean of the inhibitory zone was the 50% concentration of cocoa bean husk extract group (17.07 mm ± 1.01), but lower than CHX. The lowest inhibitory zone was the 12.5% (10.12 ± 0.05 mm). Conclusion: The cocoa bean husk extract has antibacterial activity on the growth of Streptococcus alpha, but it is lowerthan Chlorhexidine Gluconate.Keywords: cocoa bean husk extract; antibacterial activity; S. alpha’s growth; child’s dental plaque